The Ethics of Genetic Screening in the Workplace - Kupfer, Joseph (Business ethics quarterly, 1993)
This paper clarifies the nature of genetic screening and morally evaluates using it to deny people employment. Four sets of variables determine screening’s ability to forecast disorder. The first two concern epistemological limitations: whether the gene itself has been located; whether knowledge of other family members is necessary. The latter two refer to genetic causality: whether other genes are needed; whether the gene causes the disorder or just a susceptibility to it.Considerations of privacy and justice warrant restricting screening to job-specific disorders, without prejudice to the worker. Screening is more of an invasion of privacy than most “searches” because our very selves are disclosed; serious stigmatizing can result. It is unjust to penalize someone for a susceptibility to a disorder. It is also unjust to use the genetic knowledge and technology, developed with public monies allocated for public good, against members of the public.